2013
DOI: 10.1159/000348319
|View full text |Cite
|
Sign up to set email alerts
|

Device-Related Thrombus Overlying a Left-Atrial Occlusion Device Implanted for Persistent Spontaneous Echo Contrast despite Prolonged Oral Anticoagulation Therapy

Abstract: A 75-year-old woman with a history of atrial fibrillation, severe biatrial enlargement, persistent dense spontaneous echo contrast in the left atrium and left-atrial appendage on appropriate oral anticoagulant therapy underwent implantation of the left-atrial occlusion device to decrease her risk of thromboembolic stroke. Six weeks later, a scheduled transesophageal echocardiography showed a partially mobile mass (4.1 × 2.1 cm) overlying the atrial surface of the device: a suspected thrombus. This report highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(11 reference statements)
2
3
0
Order By: Relevance
“…Consistently with a case report by Elabbassi et al describing a 75-year-old woman with device-related thrombus overlying a LA occlusion device implanted in the presence of persistent spontaneous contrast despite prolonged OA, we observed spontaneous contrast in the LA in pre-procedural and follow-up TEE examinations in our patient [13]. In line with the findings of the above studies, it is recommended to perform TEE at 45 days to 6 months after the implantation, since most thrombi were documented so far at 45-day TEE [5].…”
Section: Case Reportsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistently with a case report by Elabbassi et al describing a 75-year-old woman with device-related thrombus overlying a LA occlusion device implanted in the presence of persistent spontaneous contrast despite prolonged OA, we observed spontaneous contrast in the LA in pre-procedural and follow-up TEE examinations in our patient [13]. In line with the findings of the above studies, it is recommended to perform TEE at 45 days to 6 months after the implantation, since most thrombi were documented so far at 45-day TEE [5].…”
Section: Case Reportsupporting
confidence: 92%
“…Therefore, anticoagulant therapy is recommended in all patients with device-associated thrombus regardless of the symptoms until thrombus resolution is confirmed by follow-up TEE [5]. As reported by Elabbassi et al and observed in our patient, this kind of treatment regimen is not always successful, especially in patients with permanent AF, large LA and dense spontaneous echo contrast in TEE [13].…”
Section: Case Reportsupporting
confidence: 44%
See 1 more Smart Citation
“…Prophylactic anticoagulation decreases the risk of a thrombotic event, but it remains elevated until blood viscosity returns to normal [ 1 ]. Thrombus formation, despite adequate oral anticoagulation, was previously described in a patient with persistent spontaneous echo contrast [ 14 ]. Spontaneous echo contrast is the reflection of erythrocyte aggregation, which we described as the consequence of increased blood viscosity [ 15 ].…”
Section: Reviewmentioning
confidence: 99%
“…Although percutaneous coronary intervention (PCI) with DES has been widely used to treat patients with symptomatic coronary artery disease (CAD) all over the world, recent studies have raised concerns about its long-term clinical safety and efficacy, which remains a challenge for interventional cardiologists, including delayed arterial healing response, in-stent restenosis, late stent thrombosis and the local inflammatory reactions [2,3,4]. Moreover, the systematic pro-inflammatory response after PCI with DES is still poorly defined.…”
Section: Introductionmentioning
confidence: 99%